Study of ternary glass spherical particle beds: porosity, tortuosity, and permeability - Dias, Ricardo P. (2005)
Ternary mixtures of glass beads were constructed as a model of granular packing. Porosity and permeability were experimentally determined in a wide range of mixture composition. Based on experimental data, tortuosity was calculated using the Kozeny-Carman equation. Applying the conventional relation that expresses tortuosity as the inverse of the power order of porosity, it was found that the parameter n varies with the fraction content. The observed phenomenon was explained by wall effects between particles of different sizes.